Africa Digest : Trends and issues in business Vol. 4 - Burger, Johan (2020)
The Africa Digest is a fortnightly e-newsletter scanning the key trends in the macro-environment and industry to promote knowledge and raise understanding of business in Africa. This issue explores 1. Trends on China in Africa - China’s presence in Africa is the topic of many papers, articles and arguments. Over the past few years, the Chinese government and its private sector became major players on the continent in trade, investments, and support for African governments. 2. Financial services in Africa - Many of Africa’s local financial services companies fail to adequately serve the needs of their clients, with obvious exceptions such as a number of banks in South Africa, Eco Bank with its head office in Ghana, and the Equity Bank Group in Kenya. Some African countries host a number of smaller banks that are under hard-pressed to survive, which tends to tarnish the image of the sector. Also, banks based in developed countries may hesitate to support efforts by their clients to expand into Africa. These gaps create opportunities for other banks to serve clients seeking to fund expansion, such as Singapore-based Standard Chartered. However, many foreign corporations still find funding a barrier to their ambitions to foray into Africa. 3. Western companies in Africa -China is not the only player that taps the investment opportunities available in Africa. In sectors such as retail, global players based in the West are increasing their footprint. Other companies seek to fill gaps in attractive sectors on the continent where global players either are absent or have a low profile. 3. Fintech and mobile money in Africa - Africa’s fintech and mobile money subsector shows at least two decades of consistent growth, increasing the level of financial inclusion in many African countries, with Kenya the leading example of this phenomenon. Fintech’s success also disrupts the market for many retail banks in a number of African countries, raising the spectre of disintermediation. 4. Linking Africa to the world - Africa must increase its exposure to the world at large, if it wants to grow its economies and deal with challenges in the industrialisation of its agriculture and manufacturing sectors, to name but two. Developments in ICT, developing food security, building out its infrastructure (transport, energy, water, housing, hospitality, etc.) and increasing the sophistication of technology use will require Africa to reach out and partner with foreign countries and corporations. This paper looks at potential partners, including both Western and non-Western governments, but excluding China (government and private sector companies) and private sector corporations based in the traditional colonial powers.